The Philosophy of Liberty in the Star Wars Movies – Part 2 - Catharino, Alex (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
The article analyzes the Moral Philosophy and the Political Theory in the Star Wars movies saga, created by the moviemaker George Lucas. The author relates Anakin Skywalker fall with the ascension of the Galactic Empire and discusses some of the story issues that may be appropriated as metaphoric explanations of some theoretical proposals of the Austrian School of Economics, especially Ludwig von Mises’ and F. A. Hayek’s ideas.